Clinical and MRI features of Japanese patients with multiple sclerosis positive for NMO-IgG. Issue 9 (27th February 2006) - Nakashima, I; Fujihara, K; Miyazawa, I; Misu, T; Narikawa, K; Nakamura, M; Watanabe, S; Takahashi, T; Nishiyama, S; Shiga, Y; Sato, S; Weinshenker, B G; et al.
Abstract : This study investigates the relation between the serological status of NMO (neuromyelitis optica)-IgG and the clinical and MRI features in Japanese patients with multiple sclerosis. Serum NMO-IgG was tested in 35 Japanese patients diagnosed with multiple sclerosis, including 19 with the optic–spinal form of multiple sclerosis (OSMS), three with the spinal form of multiple sclerosis (SMS), and 13 with the conventional form of multiple sclerosis (CMS), which affects the brain. NMO-IgG was detected in 14 patients, 12 with OSMS and 2 with CMS. In these patients, longitudinally extensive (>3 vertebral segments) spinal cord lesions (93% v 57%) and permanent, complete blindness (no perception of light) in at least one eye (50% v 0%) were the noticeable features as compared with NMO-IgG-negative OSMS. The two patients having CMS with NMO-IgG had unusual brain lesions, but in other respects had features suggesting OSMS. NMO-IgG was detected in more than half the number of patients with OSMS and in some patients with CMS. This newly discovered serum autoantibody was markedly associated with longitudinally extensive spinal cord lesions and with complete blindness, suggesting severe optic–spinal disease.